Technologie wspomagające a umiejętności społeczne - Myck-Wayne, Janice; Ramirez, Scott (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2014)
Everyday new technology is changing the lives in ways we never imagined. For individual with autism spectrum disorder (ASD), some new technologies can improve communication, assist in the development of social skills and enhance the ability to learn. This paper discusses the concepts of Universal Design for Learning as a context for exploring the use if assistive technology in supporting the developmental of social skill training for children with ASD.